Alterations in the pulmonary histoarchitecture of neonatal mice exposed to hyperoxia - Renata B. Reis; Akinori C. Nagato; Clarissa R. Nardeli; Isadora C.P. Matias; Wanderson G. Lima; Frank S. Bezerra (Brazilian Society of Pediatrics, 2013)
Objectives: To analyze the effects of exposure to hyperoxia (100% oxygen) on the lung histoarchitecture of neonatal mice. Methods: Neonatal Balb/c mice were exposed to hyperoxia (HG) (100% oxygen) (n = 10) in a chamber (15 x 20 x 30 cm) for 24 hours with a flow of 2 L/min. The control group (CG) (n = 10) was exposed to normoxia in the same type of chamber and for the same time. After exposure, the animals were euthanized by decapitation; the lungs were removed and processed for histological examination according to the laboratory routine. Three-mm thick sections were stained with hematoxylin and eosin (H&E). The morphometric analysis was performed with in order to analyze the macrophages present in the alveolar lumen, surface density (Sv) of gas exchange, volume density (Vv) of lung parenchyma, and areas of atelectasis. Results: A decrease in the number of alveolar macrophages (MØ) was observed in the HG (HG = 0.08±0.01 MØ/mm2, CG = 0.18 ± 0.03 MØ/mm2, p = 0.0475), Sv of gas exchange in HG (HG = 8.08 ± 0.12 mm2/mm3, CG = 8.65 ± 0.20 mm2/mm3, p = 0.0233), Vv of lung parenchyma in HG (HG = 54.7/33.5/83.5%/ mm2; CG = 75/56.7/107.9%/mm2, p < 0.0001) when compared with the CG. However, there was an increase in areas of atelectasis in HG (HG = 17.5/11.3/38.4 atelectasis/mm2, CG = 14/6.1/24.4 atelectasis/mm2, p = 0.0166) when compared with the CG. Conclusion: The present results indicate that hyperoxia caused alterations in lung histoarchitecture, increasing areas of atelectasis and diffuse alveolar hemorrhage.